Moral Catalyst in Audit: The Selective Role of Auditor's Sense of Responsibility in Strengthening the Effectiveness of Fraud Detection - Krissantono Karo Karo; Cris Kuntadi (Dinasti International Journal of Digital Business Management, 2026)
This study examines the effect of auditor competence, independence, and experience on fraud detection, with Auditor's Sense of Responsibility (ASOR) as a moderating variable. A survey of 238 external auditors at Public Accounting Firms (KAP) in Jakarta was analysed using Structural Equation Modeling–Partial Least Square (SEM-PLS) with a Higher Order Construct (HOC) approach. Results indicate that competence (β = 0.448; p = 0.000), experience (β = 0.402; p = 0.000), and independence (β = 0.244; p = 0.000) each significantly and positively influence fraud detection. ASOR alone does not significantly affect fraud detection (β = −0.057; p = 0.212). In moderation tests, ASOR does not significantly strengthen the effect of competence (β = 0.003; p = 0.938); however, it partially moderates the effects of independence (β = 0.177; p = 0.000; VAF = 42.0%) and experience (β = 0.214; p = 0.000; VAF = 34.7%). The model explains 67.2% of the variance in fraud detection (R² = 0.672; SRMR = 0.022). This study contributes to forensic audit literature by demonstrating that ASOR functions as a psychological reinforcer that selectively strengthens independence and experience but not technical competence that is already independently internalized.